Frailty, disability, and mortality in a rural community-dwelling elderly cohort from Northern India - Rama Shankar Rath; Rakesh Kumar; Ritvik Amarchand; Giridara P Gopal; Debjani Ram Purakayastha; Reshmi Chhokar; Venkatesh V Narayan; A B Dey; Anand Krishnan (Wolters Kluwer Medknow Publications, 2021)
Introduction: With increasing proportion of the elderly in the world, detecting and preventing frailty assumes importance to improve the quality of life and health. The study aimed to estimate the prevalence of frailty, disability and its determinants and their relation with mortality among community dwelling elderly cohort. Materials and Methods: The study was conducted in a cohort in rural Haryana, India, and was followed till October 2018. Frailty was assessed using the Edmonton Frailty Scale and disability was assessed using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) scale by trained physicians. Results: The prevalence of frailty was found to be 47.3% (95% confidence interval [CI]: 44.0-50.8). The median WHODAS-2 score was found to be 10.4 (2.1-29.2). Those who were older (odds ratio [OR] - 2.5; 95% CI: 1.8-3.4), women (OR - 3.3; 95% CI: 2.2-4.9) and those with chronic disease (OR 2.3; 95% CI: 1.7-3.1) had higher rates of frailty. The adjusted hazard ratio of death among frail people was 4.7 (2.3-9.7). Conclusion: In this study we found the frailty is associated with the mortality among community dwelling elderly. Thus early identification of the frailty and its determinants may help us to reduce the mortality related to this.